Економіко-правові основи аудиту в Україні - Щирба, Маркіян; Shchyrba, Markiyan (ТДЕУ, 2006)
Обґрунтовано необхідність і розкрито сутність аудиту в ринкових умова господарювання. Проведено аналіз економіко-правового забезпечення аудиту в Україні. There have been founded necessity and revealed substance of auditing in market economy. The article parses and reveals structure of economical and foundations of auditing in Ukraine.
Economic-lawer bases of audit in Ukraine